Penerapan Model Picture and Picture untuk Meningkatkan Motivasi Belajar dan Keterampilan Menulis Teks Naratif Pada Siswa Kelas VII MTs Negeri 5 Sleman - Apriyani, Nur Endah Dwi; Ermawati, Ermawati; Rufaidah, Desy (Wacana Akademika: Majalah Ilmiah Kependidikan, 2023)
The research aims to describe the learning motivation and learning outcomes of students with the application of picture and picture model on narrative text. Data collection techniques in this study used tests, questionnaires, and documentation. Data analysis techniques in this study are qualitative data analysis techniques and quantitative data analysis techniques. The results of learning motivation in pre-cycle activities were 51.33%, in cycle I it was not maximized with a result of 74.58%, and in cycle II it increased with a final result of 83.61%. The results of pre-class activities on narrative text writing skills were 57.85%, in cycle I experienced a slight increase with a result of 70%, and in cycle II experienced an increase with a result of 80%. Based on the description above, it can be concluded that learning narrative text writing skills using the picture and picture model can increase learning motivation and learning outcomes of students in class VII-B MTs Negeri 5 Sleman.